Personal and professional pain experiences and pain management knowledge among Greek nurses - Papathanassoglou, Elizabeth; Patiraki, Elisabeth; Tafas, Cheryl (My University, 2004)
The purpose of this exploratory study was to describe Greek registered nurses' personal and professional pain experiences and to examine the relationship with their pain management knowledge. Forty-six Greek nurses provided written responses to open-ended questions about their personal and professional experiences with pain and beliefs about suffering. Reporting a personal pain experience was associated with describing a positive professional pain experience, Φ=0.44, p<0.03. The nurses vividly described their personal and professional pain experiences. One nurse wrote "...I begged to lose consciousness, in order not to feel". These compelling accounts might motivate nurses to strengthen their understanding of pain management
Keywords: Nursing--Studies and exercises; Pain; Greece; Nurses--Attitudes; Educational tests and measurements; Nursing--Research